Budgetary Slack Behavior: The Effect of Organizational Commitment, Organizational Culture, and Environment Uncertainty - Mukhtaruddin; Hendra Susanto; Zahratunnisa; Asfeni Nurullah (Jurnal Kajian Akuntansi, 2025)
Budgetary slacks are individuals behavior in company may deviate from the budget by projecting a higher budget for spending and a smaller budget for revenue. The individual's goal in performing budgetary slacks is to facilitate the achievement of the desired targets. The aims of this study are to investigate the effect of organizational commitment and organizational culture on budgetary slack and environmental uncertainty as a moderating variable. The samples are selected by purposive random sampling. The selected samples are the nine of Stated-Owed Company (SOC) in Palembang City's with 60 respondents. The moderating regression analysis is used to answer the research questions. The data are collected by the questioners that distribute to respondent. The research finding indicated that organizational commitment has a negative impact on budgetary slack and organizational culture has a positive impact. Environmental uncertainty is lowers the impact of organizational culture and strengthens the impact of organizational commitment on budgetary slack. SOC must build a good organizational commitment and organizational culture, and also consider environmental uncertainty, as these three variables influence the likelihood of budget slack behavior. The limitations of this study are (1) the questionnaire used was closed, ensuring that respondents' responses matched the answer options; (2) the budgetary slack is only explained by commitment and organizational culture; other variables are not examined; and (3) the research was limited to SOC cluster industry in Palembang City's.